The Influence of Organizational Culture and Work Environment on the Performance - Mellinda, Septiana (Universitas Negeri Makassar, 2024)
This research aims to determine the effect of Organizational Culture and Work Environment on the Performance of Human Resources bureau employees Audit Board of the Republic of Indonesia (BPK). This research uses data through the distribution of research questionnaires, secondary data through journals and books. This study uses a probability technique in a simple way. The sample in this study were employees of the Bureau of Human Resources of BPK, totaling 67 people. The data analysis technique used in this research is Multiple Linear Regression to find the correlation coefficient, and the effect of independent variables on the dependent variable. Analysis of statistical test results using alpha = 0.05. The results showed that Organizational Culture had a significant positive effect on the Performance of BPK Human Resources Bureau Employees, the Work Environment had a significant positive effect on the Performance of BPK Human Resources Bureau employees, and simultaneously Organizational Culture and Work Environment had a significant positive effect on the Human Resources Bureau's employee performance. This means that the contribution of Organizational Culture and Work Environment to the Performance of HR Bureau Employees is 69%, while the remaining 31% is explained by other variables not examined in this research.